Identifying barriers to institutional change in disability services - Ágota Scharle; Balázs Váradi (WWWforEurope, 2013)
In a comparative framework, the paper uses a recently observed shift away from cash transfers and towards the provision of rehabilitation services to identify barriers to welfare policy reform. The analysis relies on the assumption that some European welfare regimes have a similar initial structure but may differ in their speed of adaptation to the challenges posed by external shocks. A detailed comparison of fast moving and slow moving countries allows us to identify some of the barriers to change. Throughout the analysis, we focus on provisions for people with disabilities, where the above shift has been observed, and with much variation across member states. Comparing policy developments in Finland, Norway, and Sweden in the past twenty years we identify fiscal constraints, historical commitment to equal rights, policy making capacity, and centralisation as important drivers of change. While some of these factors are beyond the control of policy makers, some can be strengthened by governments wishing to improve the long term performance of the welfare system.
Keywords: I38; D78; H75; 330; Academic research; challenges for welfare system; good governance; institutional reforms; labour markets; multi-level governance; policy options; political economy of policy reform; social development; social innovation; welfare reform; welfare state